PERSEPSI MASYARAKAT TENTANG KEARIFAN LOKAL LUBUK LARANGAN DI DESA PADANG SAWAH KECAMATAN KAMPAR KIRI - Wahyuni, Sri; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the implementation of the local customs prohibitions in the village of rice fields Kampar left and for know how the public’s perception of the value of local wisdom of the tradition of the village the left Kampar. Respondents in this study were 50 people using purposive sampling techniques. The data collection techniques that are done are observation, polls, and interviews. This from of research is a qualitative descriptive. The method of study used is the mixed method. this method is done by collecting data and analysis of qualitative data at a later stage to reinforce the research results. Based on the results of the research conducted on the public perception of local wisdom in the village of rice field prohibition in the left Kampar district, it can be concluded that the overall data on public perception about local wisdom under the prohibition of many states that the tradition of a ban is very good prohibition of 86,14%. Based on the results of the research and analysis of data, the researchers give recommendations to the community of rice fields should be more concerned about the tradition of a prohibition in kampar, especially in the village of rice field Kampar left district.Key Words: Local Wisdom, Lubuk Ban